Implementasi Undang-Undang Nomor 22 Tahun 2022 Tentang Pemasyarakatan Oleh Petugas Pengamanan Terhadap Wargabinaan Di Lembaga Pemasyarakatan Kelas IIB Muara Teweh Kabupaten Barito Utara Kalimantan Tengah - Edie Saputra; Elwidarifa Marwenny (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Correctional Institutions (LAPAS) play a crucial role in Indonesia's correctional system, tasked with rehabilitating Correctional Inmates (WBP) to reintegrate productively into society. However, the issue of overcapacity in LAPAS Class IIB Muara Teweh poses significant challenges in security management and inmate rehabilitation, including the heavy workload of security officers. Based on data, this LAPAS houses 383 inmates, far exceeding its ideal capacity of 175, with a security ratio that is highly imbalanced (ideally 1 officer for every 5 inmates). This increases the risks of conflicts, escapes, and security disturbances. This research examines the role of security officers in managing inmate security, the challenges faced by security officers in performing their duties, and the effectiveness of security personnel in providing protection at LAPAS Class IIB Muara Teweh. The research employs a qualitative method with an Empirical Juridical approach and a case study (Case Approach). The results reveal that security officers play a strategic role in maintaining order and supporting rehabilitation, but their main challenges include a lack of personnel, insufficient facilities, and high workloads. The effectiveness of security is hindered by the imbalanced ratio and limited training. Therefore, efforts are needed to improve the competence of security personnel, increase staffing and facilities, and conduct regular performance evaluations to create a safer and more conducive environment in LAPAS. This study is expected to serve as a reference for future correctional facility management policies in Indonesia